Romania's Foreign Trade Between 1945 and 1989 - Andrei-Cristian Balasan (CES Working Papers, 2013)
In this paper we have analysed a “special” period in the history of Romania's trade, namely the period when market economy was replaced by the state economy. It is the period preceding the transition. We analysed how Romania's exports and imports have evolved between 1945 and 1989, highlighting the events that influenced trade, and also what changes occurred in the structure of exports and imports by product groups and, not least, who were the main external partners of Romania.
Keywords: F1; O24; O52; 330; foreign trade; export; import; trade balance Romania